The effectiveness of a practical half-time re-warm-up strategy on performance and the physical response to soccer-specific activity - Fashioni, E.; Langley, B.; Page, R. M. (Journal of Sports Sciences, 2020)
The aim of this study was to assess the influence of a half-time (HT) re-warm up (RWU) strategy on measures of performance and the physical and perceptual response to soccer-specific activity. Ten male soccer players completed a control (CON) and RWU trial, in which participants completed 60 min (4 x 15-min periods with a 15-min HT interspersing the third and fourth periods) of a soccer-specific exercise protocol. The CON trial comprised a passive 15-min HT, whilst the RWU trial comprised a passive 12-min period, followed by a 3-min RWU. The RWU elicited an improvement in 20 m sprint times (d= 0.6; CON: 3.42 ± 0.20 s; RWU: 3.32 ± 0.12 s), and both squat (d= 0.6; CON: 26.96 ± 5.00 cm; RWU: 30.17 ± 5.13 cm) and countermovement jump height (d= 0.7; CON: 28.15 ± 4.72 cm; RWU: 31.53 ± 5.43 cm) following the RWU and during the initial stages of the second half. No significant changes were identified for 5 m or 10 m sprint performance, perceived muscle soreness, or PlayerLoadTM. Ratings of perceived exertion were however higher (~2 a.u) following the RWU. These data support the use of a HT RWU intervention to elicit acute changes in performance.